Angioimmunoblastic T-cell lymphoma mimicking drug fever and infectious etiology after a thyroidectomy: A case report. Issue 34 (August 2019) - Han, Ping; Yang, Lan; Yan, Wei; Tian, Dean
Abstract: Introduction: Angioimmunoblastic T-cell lymphoma (AITL) is a rare subtype of mature peripheral T-cell lymphoma and accounts for approximately 1% to 2% of non-Hodgkin lymphomas. Although the B symptoms with generalized lymphadenopathy are the most frequent manifestations of AITL, its diagnosis remains a challenge as clinical manifestations and pathological features are frequently misleading. Patient concerns: We report herein the case of a 70-year-old man with intermittent fever, pulmonary infection, and skin rash developed for 1 month before admission. Previously, he had undergone thyroidectomy for thyroid papillary carcinoma. Fever occurred on the day of discharge and occurred again during the next month. Symptoms worsened despite treatment with antibiotics and papular rash appeared. The local hospital diagnosed it as drug fever and stopped all antibiotics. Fever and rash were controlled temporarily; however, both relapsed 2 days before admission. On the night of admission, the patient developed fever again. Blood culture showed Staphylococcus epidermidis and Staphylococcus haemolyticus infection. Interventions: Taking into account the recent history of surgery, the patient was diagnosed with septicemia and was treated with anti-infective treatment. On 13th day after admission, the patient developed fever again accompanied by generalized lymphadenopathy. However, multiple blood cultures were negative and bone marrow aspiration cytology, biopsy, immunohistochemistry, and gene rearrangement results were normal. Diagnosis: The patient was finally subjected to cervical lymph node biopsy and was diagnosed with AITL. Outcomes: The patient was transferred to the Department of Hematology for further treatment. Conclusion: This case highlights the complex diagnostic challenges of AITL. AITL accompanied by thyroid carcinoma may not be a mere coincidence and administration of antibiotics may be a rare cause of AITL. Abstract : Supplemental Digital Content is available in the text